CAPUNG DALAM KARYA TAPESTRI - Drs. Erwin A, M.Sn., INDRI YANI SOS PUTRI 1301039, Dra. Minarsih, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2017)
Dragonflies are one of the insects that have uniqueness and beauty in terms of body anatomy, color, nature and activity of dragonfly in his life. When viewed from the meaning of beauty to be a unique and beautiful dragonfly, this insect passes through a series of life cycles. In addition, the characteristics of the dragonfly is something interesting to be an inspiration in creating works of art that is tapestry techniques.The creation of this work aims to visualize the beauty of a dragonfly in its life activities. This tapestry works using soumak techniques, giordes, klim, and combined with the material stockings on the wings of dragonfly.After performing a series of long creation process, there are 7 pieces of tapestry, such as: 1) Dragonflies, 2) Snatching, 3) Marriage, 4) Laying eggs, 5) Dragonfly, 6) Interacting, 7) Pairing. Through tapestry works with the theme of the life of dragonflies is expected to arouse the spirit in the work of art, and used as a reference and reference to create a better work tepestri future.Keywords: Dragonflies, Tapestries, Embroidery